2008
DOI: 10.1111/j.1365-3059.2008.01838.x
|View full text |Cite
|
Sign up to set email alerts
|

Cucumber mosaic virus infection of chickpea stands: temporal and spatial patterns of spread and yield‐limiting potential

Abstract: Patterns of spread and yield losses were examined when migrant aphid vectors transmitted Cucumber mosaic virus (CMV) within chickpea ( Cicer arietinum ) plots. When numbers of chickpea plant infection foci were varied to provide initial infection incidences of 0·3-2%, rate of virus spread and its final incidence increased in proportion to initial virus incidence and pathogen progress curves reflected a polycyclic pattern of spread. Chickpea seed yields decreased by 44-45% when CMV incidence reached 61-74% at f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 31 publications
1
21
0
1
Order By: Relevance
“…Losses are generally greatest when plants become infected at vulnerable early growth stages and incidence approaches 100%. Examples of quantitative estimates of seed yield losses from field experiments with natural spread include ones with CMV and BYMV in lupin where yield losses of up to 66% occurred (Bwye, Jones, & Proudlove, 1994;Jones, 2001;Jones, Coutts, & Cheng, 2003), CMV in chickpea where yield losses were up to 80% ( Jones, Coutts, Latham, & McKirdy, 2008), and PSbMV in pea where yield losses of up to 25% occurred (Coutts, Prince, & Jones, 2009). Yield losses from field experiments with other combinations of virus and cool-season grain legume crops are given by Alkhalaf, Kumari, Haj Kasem, Makkouk, and Al-Chaabi (2010), Boswell and Gibbs (1983), Bos et al (1988), Cockbain (1983), Franz, Makkouk, and Vetten (1997), Kraft and Hampton (1980), Kumari and Makkouk (1995), , Makkouk, Kumari, and Bos (1993), and .…”
Section: Fb P Le Cpmentioning
confidence: 99%
“…Losses are generally greatest when plants become infected at vulnerable early growth stages and incidence approaches 100%. Examples of quantitative estimates of seed yield losses from field experiments with natural spread include ones with CMV and BYMV in lupin where yield losses of up to 66% occurred (Bwye, Jones, & Proudlove, 1994;Jones, 2001;Jones, Coutts, & Cheng, 2003), CMV in chickpea where yield losses were up to 80% ( Jones, Coutts, Latham, & McKirdy, 2008), and PSbMV in pea where yield losses of up to 25% occurred (Coutts, Prince, & Jones, 2009). Yield losses from field experiments with other combinations of virus and cool-season grain legume crops are given by Alkhalaf, Kumari, Haj Kasem, Makkouk, and Al-Chaabi (2010), Boswell and Gibbs (1983), Bos et al (1988), Cockbain (1983), Franz, Makkouk, and Vetten (1997), Kraft and Hampton (1980), Kumari and Makkouk (1995), , Makkouk, Kumari, and Bos (1993), and .…”
Section: Fb P Le Cpmentioning
confidence: 99%
“…The role of annual weeds and weed seed is less clear. Seed transmission of AMV, CMV, BYMV and PSbMV in a number of pulse crops is well established (Abraham and Makkouk 2002;Makkouk et al 1993;Jones and Coutts 1996;McKirdy et al 2000;Latham et al 2001;Latham and Jones 2001b;Parry and Freeman 2001) and infected pulse seed often provides the primary inoculum for aphids to spread virus within crops (Latham and Jones 2001a;Latham and Jones 2001b;Jones et al 2008;Coutts et al 2009). A survey of chickpea, fababean, field pea and lentil seed used on farm in 1997 in the Wimmera and Mallee regions of Victoria showed that Malva parviflora, Medicago spp., Raphanus raphanistrum, Sonchus spp., and Vicia sativa seeds were common as contaminants in pulse grains (Moerkerk 2002).…”
Section: Introductionmentioning
confidence: 98%
“…Les pays de l'Afrique de l'Ouest et du Centre contribuent pour plus de 90% à la production annuelle mondiale évaluée à 38 millions de tonnes d'ignames (FAO, 2007 (Odu et al, 2004). En effet, ces deux (2) virus affectent sérieusement les rendements de cette culture (Thouvenel et Dumont, 1990;Asiedu et al, 1998 ;Eni et al, 2008a;Jones et al, 2008 ;Séka et al, 2009). Thouvenel et al (1989) et Kouamé et al (2003) ont montré que dans la zone savanicole de la Côte d'Ivoire, l'incidence du YMV et du CMV diffère de celle observée en zone forestière.…”
Section: Introductionunclassified